Extracellular mass to body cell mass ratio association to nutritional and functional status in middle-aged and older adults - Cano, Antonella; Ventura, Lucia; Catte, Maria Grazia; Castiglia, Elena; Sanna, Josetta; Martinez, Gianluca; Oneto, Carmen; Loi, Nicola; Ginatempo, Francesca; Manca, Andrea; Deriu, Franca (Frontiers in Nutrition, 2025)
IntroductionPoor nutrition and progressive loss of muscle mass is frequent in older individuals. Extracellular mass to body cell mass ratio (ECM/BCM), an easy to calculate index obtained by bioelectrical impedance vector analysis (BIVA), is a parameter of catabolism or extracellular mass expansion, mainly studied in pathological conditions. The aim of the study was to characterize ECM/BCM ratio and its association to indexes of nutritional and functional status in middle-aged and community dwelling older individuals.MethodsParticipants aged 51–89 years old (n = 158, 96 women) were included in the study. Comorbidity burden was assessed by Charlson comorbidity index. Nutritional status was evaluated by mini nutritional assessment (MNA) and BIVA. Plasma biochemical parameters were measured, and prognostic nutritional index (PNI) and geriatric nutritional risk index (GNRI) were calculated. Functional performance was assessed by hand dynamometry and evaluated by means of muscle quality index (MQI).ResultsECM/BCM mean value was 0.91 ± 0.12. Higher values were observed in women and in individuals over 75. Subjects displaying ECM/BCM above median, presented significantly lower MNA score, PNI, GNRI, and MQI (all p ≤ 0.05), compared to individuals with ECM/BCM values below median. Linear regression model using ECM/BCM, age, and sex as independent factors, showed ECM/BCM as significantly associated to comorbidity burden (β = 0.175, p = 0.019); MNA (β = −0.285; p = 0.004), PNI (β = −0.253; p = 0.009), GNRI (β = −0.363; p < 0.0001) and MQI (β = −0.311, p = 0.0001).DiscussionHerein, ECM/BCM has been associated, after adjusting for cofounding factors as age and sex, to subjective and objective indexes of health, nutritional and functional status in middle-aged and community dwelling older adults. With an integrated perspective, it could represent an easy to calculate, objective index to assess and monitor health, nutritional and functional status in this population.